Investigating the Foundations of Sufism-Based Education in the Qur’an and Hadith - Subhan Abdullah Acim (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
This article focuses on the discussion on the basis of Sufism-based education from the perspective of the Qur'an and hadith. This article is the result of a literature review by relying on data in the form of Islamic books and scientific journals. This study is guided by two problem formulations: first, what are the basic foundations of Sufism education in the Qur'an; Second, what is the basic foundation of Sufism education in hadith. this study shows that the verses that support Sufism-based education are Surah al-A’la: 14-15 and Surah al-R’'d: 28. These verses show that remembrance is a tradition commonly practiced by Sufis. Zikr is one method of purifying the soul (tazkiyah al-Nafs) and calming the heart (ithmainn al-Qalb). In addition to the Qur’an, a number of hadiths indicate that the practice of loud remembrance (jahr) and silent voice (sirr) is part of the Sufistic tradition. Even the sirr and jahr remembrance models have been practiced in the lifetime of the Prophet Muhammad. Zikr in congregation, and with a certain number of remembrance numbers, was also practiced at the time of the Prophet.